1995
DOI: 10.1111/j.1440-1835.1995.tb00007.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of the order Bangiales (Bangiophycidae, Rhodophyta) based on sequences of nuclear small‐subunit ribosomal RNA genes

Abstract: SUMMARY We investigated phylogenetic relationships among red algae of the order Bangiales by analysis of sequences of the nuclear gene encoding cytosolic small‐subunit ribosomal RNA in Bangia atropurpurea (Roth) C. Ag. and eight samples representing seven species of Porphyra. The ssu‐rDNA range from 1818 to 1845 nucleotides in length, with guanosine plus cytosine ratios between 47.0% and 48.6%. A group IC1 intron occurs in the B atropurpurea ssu‐rDNAs at the same position as in P. spiralis var. amplifolia Oliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 42 publications
1
40
0
2
Order By: Relevance
“…All three phylogenetic analyses -MP, ME and MLgenerated trees with similar structure (Figs 14 and 15). In all trees Porphyra and Bangia are paraphyletic with respect to one another, as well established by Oliveira et al (1995), Mu¨ller et al (1998), andBroom et al (1999). A basal subdivision within the Bangiales is well supported in all trees, as has been observed in previous analyses of nSSU sequences from the order (Broom et al, 1999(Broom et al, , 2004Mu¨ller et al, 2001a).…”
Section: Sequence Datamentioning
confidence: 63%
See 2 more Smart Citations
“…All three phylogenetic analyses -MP, ME and MLgenerated trees with similar structure (Figs 14 and 15). In all trees Porphyra and Bangia are paraphyletic with respect to one another, as well established by Oliveira et al (1995), Mu¨ller et al (1998), andBroom et al (1999). A basal subdivision within the Bangiales is well supported in all trees, as has been observed in previous analyses of nSSU sequences from the order (Broom et al, 1999(Broom et al, , 2004Mu¨ller et al, 2001a).…”
Section: Sequence Datamentioning
confidence: 63%
“…All sequences, except that of entity ZEK881, included a group I intron, inserted at the nSSU position equivalent to base 516 in Escherichia coli, as is common in Porphyra and Bangia (Oliveira & Ragan, 1994;Oliveira et al, 1995;Mu¨ller et al, 1998Mu¨ller et al, , 2001aBroom et al, 1999). Complete sequences of introns were obtained for at least one specimen from each V9 entity, except for ZAE953 and ZLI1045, for which sequences were only partial.…”
Section: Sequence Datamentioning
confidence: 99%
See 1 more Smart Citation
“…raulaguilarii mentioned here. Table 2 shows the vegetative and reproductive characters of various species of Pyropia and in it observed the (Stiller & Waaland 1993, Oliveira et al 1995, Broom et al 1999, Kunimoto et al 1999 have revealed considerable interspecies diversity of the nrSSU and rbcL regions within this genus and suggest that provides useful characters for species identification.…”
Section: Discussionmentioning
confidence: 99%
“…This order has been considered monophyletic with the single family Bangiaceae. Traditionally, Bangia Lyngbye and Porphyra C. Agardh have been recognized on the basis of gametophyte morphology: unbranched uni-to multiseriate filaments in the genus Bangia and blade in the genus Porphyra (Oliveira et al 1995). Recently, the revision of the order Bangiales, based on the phylogeny using nrSSU and rbcL genes, has greatly improved the taxonomic understanding of this group (Sutherland et al 2011).…”
Section: Introductionmentioning
confidence: 99%